AB0758 Performance of a therapeutic attempt with oral prednisolone in patients with rheumatoid arthritis and hand osteoarthritis – a proof of concept study. (23rd January 2014) - Kiltz, U.; von Zabern, C.; Heldmann, F.; van Werde, M.; Mintrop, B.; Baraliakos, X.; Braun, J.
Abstract : Background: The differential diagnosis between an early inflammatory arthritis or rheumatoid arthritis (RA) and osteoarthritis (OA) of the hand can be difficult. Many rheumatologists are used to just perform a short therapeutic attempt with prednisolone in this situation. However, this test has never been evaluated. Objectives: To quantify and compare the efficacy of a medium dose of prednisolone in cortisone naive patients with established RA and hand OA. Methods: Thirty patients with RA (n=15) and OA (n=15) who reported hand pain and swelling were treated for 5 days with 1g paracetamol /day. On days 3-5 a morning dose of 20mg of prednisolone was added. Hand pain was quantified on a numerical rating scale (NRS 0–10), and a subjective percentage of improvement was also recorded. Based on previous experience, a cut off of 40% improvement was set to differentiate between responders and non-responders. The Mann-Whitney-U-test was used for comparison. Results: There were 13 females in the RA (86.7%) and 11 in the OA (73.3%) group. The mean age (SD) was 59.3 (6.3) and 66.8 (10.3) years, and the mean symptom duration (SD) 4 (3.5) and 10.8 (13.9) years, respectively. The mean pain scores were 5.4±1.6 vs. 5.3±1.4 on day 1, and 2.9±1.8 vs. 4.1±1.5 on day 5, respectively. The mean percentage of improvement was 52.3%±27.9 in the RA vs. 22.0%±20.1 in the OA group, respectively. There were 11 responders in the RA (73.3%) and 4 in the OA (26.7%) group (p=0.012). Conclusions: In this small study, the prednisolone test had a sensitivity and specificity for a diagnosis of RA of 73.3%. This suggests that the test may be useful in uncertain clinical situations to decide between inflammation or degeneration as cause of the present symptoms. However, caution is warranted since about every 4-5th patient with RA did not respond and every 4-5th patient with OA did respond to a medium dose of oral prednisolone. Disclosure of Interest: None Declared